Chaetomorpha antennina (Bory) Kützing derived seaweed liquid fertilizers as prospective bio-stimulant for Lycopersicon esculentum (Mill). (July 2019) - Muthu-Pandian Chanthini, Kanagaraj; Senthil-Nathan, Sengottayan; Stanley-Raja, Vethamonickam; Thanigaivel, Annamalai; Karthi, Sengodan; Sivanesh, Haridoss; Sundar, Narayanan Shyam; Palanikani, Radhakrishnan; Soranam, Ramaiah
Abstract: Plant nutrition serve as critical factors that influences plant growth and yield. Global fertilizer production and application is growing in surplus amounts, increasing the agricultural expenses and damaging the environment. Organic fertilizers, obtained from natural sources, encompass all essential plant nutrients. Application of aqueous seaweed extracts are regarded as potential plant biostimulant agents. The liquid seaweed extract of green seaweed Chaetomorpha antennina (CA-LSE) were evaluated for their biostimulant activity on seed germination and growth of tomato. The CA-LSEs were able to stimulate early emergence of tomato seeds, in addition to increasing their germination percentage and energy. They also exerted a positive influence on the vegetative growth, resulting in increased plant height, leaf-branch number and yield. The CA-LSEs were influence the plant's biochemical profile and displayed a linear increase in pigment contents (chlorophyll a & b and carotenoids), total soluble solids (TSS), phenols as well as ascorbic acid contents. The bio-stimulant potential was attributed to the elements present in CA-LSEs, elucidated by EDX analysis that revealed the presence of six elements (O, Na, Mg, S, Cl and Ca), that were essentially plant nutrients. These results support the bio-stimulant potential of C. antennina, which can be applied as a prospective bio-fertilizer that is economic, renewable, efficient and eco-friendly, and also can be regarded as a potential catalyst for the betterment of sustainable agricultural food production. Graphical abstract: Image 1 Highlights: Liquid extracts of Chaetomorpha antennina (CA-LSE) stimulated the germination potential of tomato seeds. CA-LSE primed seeds displayed higher seed biomass. Seedlings emerged out of CA-LSE primed seeds exhibited higher vigour. CA-LSEs were able to stimulate the vegetative growth and yield of tomato plants. Biochemistry of tomato plants were enhanced by seed priming effect of CA-LSE.